2010
DOI: 10.1371/journal.pbio.1000303
|View full text |Cite
|
Sign up to set email alerts
|

A Novel High-Affinity Sucrose Transporter Is Required for Virulence of the Plant Pathogen Ustilago maydis

Abstract: A novel, high-affinity sucrose transporter identified in the plasma membrane of the plant pathogen Ustilago maydis is essential for fungal virulence and successful infection of maize.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
237
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 216 publications
(244 citation statements)
references
References 53 publications
6
237
0
1
Order By: Relevance
“…2) and (3) feeding of U. maydis, which will most likely proceed via the high affinity sucrose transporter SRT1 that can outcompete host sucrose transporters based on its low K M for sucrose and will enable the pathogen to retrieve most of the sucrose. 7 Labeling of tumors and control leaves with 14 CO 2 showed that there is an increased pool of carbon in TCA cycle intermediates and amino acids, as more radioactivity remained in the organic acid and the cationic (AA) fraction in tumors articLe addeNdum articLe addeNdum reduced nitrogen into the biosynthesis of other amino acids or nucleobases in tumor tissue.…”
mentioning
confidence: 99%
“…2) and (3) feeding of U. maydis, which will most likely proceed via the high affinity sucrose transporter SRT1 that can outcompete host sucrose transporters based on its low K M for sucrose and will enable the pathogen to retrieve most of the sucrose. 7 Labeling of tumors and control leaves with 14 CO 2 showed that there is an increased pool of carbon in TCA cycle intermediates and amino acids, as more radioactivity remained in the organic acid and the cationic (AA) fraction in tumors articLe addeNdum articLe addeNdum reduced nitrogen into the biosynthesis of other amino acids or nucleobases in tumor tissue.…”
mentioning
confidence: 99%
“…This fact, plus additional insights observed at genomic, transcriptomic and proteomic level gave strong indications that RhtA acts as a specific transporter for L-rhamnose, but did not provide direct evidence. To assay transport capacity and quantify uptake kinetics, radiolabeled sugar uptake experiments can be performed with the mentioned yeast strain (Colabardini et al, 2014;dos Reis et al, 2013;Leandro et al, 2013;Sloothaak et al, 2015;Subtil and Boles, 2011;Wahl et al, 2010). This approach was followed in the present study as a final step to prove the ability of RhtA to transport L-rhamnose.…”
Section: Discussionmentioning
confidence: 99%
“…Similar phenotype analyses performed in filamentous fungi, where different sugar transporter mutant strains were studied, produced disparate results. In some cases, an altered growth phenotype could not be detected in plate assays containing the transporter's specific substrate (Forment et al, 2006(Forment et al, , 2014Vankuyk PA et al, 2004;Wahl et al, 2010), which is probably due to overlapping substrate specificities. In this regard, the most notorious case corresponds to S.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations